Proceedings of the 28th ACM International Conference on Information and Knowledge Management 2019
DOI: 10.1145/3357384.3358039
|View full text |Cite
|
Sign up to set email alerts
|

Social Cards Probably Provide For Better Understanding Of Web Archive Collections

Abstract: Used by a variety of researchers, web archive collections have become invaluable sources of evidence. If a researcher is presented with a web archive collection that they did not create, how do they know what is inside so that they can use it for their own research? Search engine results and social media links are represented as surrogates, small easily digestible summaries of the underlying page. Search engines and social media have a different focus, and hence produce different surrogates than web archives. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Social cards typically consist of a striking image, title, description, and source attribution. In prior work [3], we demonstrated that groups of social cards perform best for understanding collections. Social cards have become standard currency in the sharing culture, existing not only on social media platforms, but also in messaging apps like Apple Messages, storytelling services like Wakelet 1 , and News articles represent resources that have undergone editorial review, receiving some care in their publication.…”
Section: Introductionmentioning
confidence: 88%
“…Social cards typically consist of a striking image, title, description, and source attribution. In prior work [3], we demonstrated that groups of social cards perform best for understanding collections. Social cards have become standard currency in the sharing culture, existing not only on social media platforms, but also in messaging apps like Apple Messages, storytelling services like Wakelet 1 , and News articles represent resources that have undergone editorial review, receiving some care in their publication.…”
Section: Introductionmentioning
confidence: 88%
“…Existing web page summarisation tools, like Embed.ly and microlink , misattribute a Memento to the wrong source and fail to separate web archive branding from Memento content, so Jones et al (Jones et al, 2019) created MementoEmbed. MementoEmbed makes use of Memento headers and TimeMaps to find information about Mementos and provides added value over other services.…”
Section: Summarising Web Archive Collectionsmentioning
confidence: 99%
“…Both allow for previewing a page and allow pages to "compete for clicks" relative to rivals that might be present elsewhere on the page. Textual information is important, but a good striking image can also help readers better understand the underlying document [15]. As shown in the Twitter card from Figure 1, the title and description give the reader some idea of the information found in the underlying page, but the striking image provides the additional insight of a current map of COVID-19 infection locations, helping the user infer that not only is a visualization available at this resource, but that it is also updated to contain current information.…”
Section: Introductionmentioning
confidence: 99%